Economic evaluation of Maternal Depression Treatment in HIV (M-DEPTH) for perinatal depression among women living with HIV in Uganda: a cost-effectiveness analysis - Ryan McBain; Adeyemi Okunogbe; Rhoda K Wanyenze; Violet Gwokyalya; Glenn Wagner (BMJ Public Health)
Objective We conducted a cost-effectiveness analysis of an evidence-based collaborative care model for treatment of perinatal depression among women living with HIV in Uganda.Design Maternal Depression Treatment in HIV (M-DEPTH) is a cluster randomised controlled trial implemented from July 2019 to August 2023, during which 391 pregnant women with mild-to-severe depressive symptoms were randomised to receive stepped care for depression (M-DEPTH: behavioural and pharmacological treatments) or care as usual (CAU: hospital referral for severe cases), at one of eight public health facilities in Uganda.Methods We implemented time-driven, activity-based costing to determine the economic cost of M-DEPTH from a societal perspective, compared with CAU. Change in the prevalence of depressive disorder—from enrolment to 18 months postpartum—was quantified using the Patient Health Questionnaire, with depressive disorder assigned a disability weight according to the Global Burden of Disease project. Incremental cost-effectiveness ratios (ICERs) were expressed as cost per disability-adjusted life years (DALY) averted.Results The estimated economic cost of M-DEPTH was US$128.82 per participant, compared with $1.53 per participant for CAU. At baseline, prevalence of depressive disorder did not differ according to treatment assignment. Remission of depressive disorder was more prevalent among those assigned to M-DEPTH—across all time periods, including 18-month follow-up (aOR: 0.09; 95% CI 0.05 to 0.16; p<0.001). This yielded an ICER of $397 per DALY averted, when limiting benefits to those accrued over the study period. Sensitivity analyses generated estimates ranging from $162 to $418 per DALY averted.Conclusions M-DEPTH represents a financially feasible task-shifted model of evidence-based perinatal depression screening and treatment. The intervention is cost-effective at a willingness-to-pay threshold of less than half of median gross domestic product per capita in Uganda.Trial registration number NCT03892915.